Optical member and manufacturing method thereof
A lightweight optical member with low reflectance and wear resistance is achieved by forming a silica layer on a metal base material, addressing the shortcomings of existing optical members in stability and durability.
Patent Information
- Application Number
- JP2021562505
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-02
- Filing Date
- 2020-10-29
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2040-10-29
AI Technical Summary
Existing optical members, such as pellicle frames, lack a combination of low reflectance, stability against light irradiation, and wear resistance, and there is no suitable manufacturing method to achieve these properties effectively.
A lightweight optical member is manufactured by forming a low-reflectance treatment layer on a metal base material, followed by coating it with a silica layer to enhance wear resistance and suppress dust generation, using methods like chemical vapor deposition to form a dense silica layer with a thickness of 0.1 to 10 μm.
The optical member achieves low reflectance, stability against light irradiation, and wear resistance, while reducing dust generation and haze formation, at a relatively low cost.
Smart Images

Figure 0007600141000005 
Figure 0007600141000006 
Figure 0007600141000007
Abstract
Description
[Technical Field]
[0001] The present invention relates to an optical member whose surface reflectance is required to be reduced, and a method for producing the same. [Background technology]
[0002] Optical members used in various optical components (such as housings, various supports within the housing, shutter blades, and apertures) that make up optical devices such as digital cameras, digital video cameras, and camera-equipped mobile phones are required to be lightweight and highly rigid, as well as have low surface light reflectance, and it is common for the surface to have a high degree of blackness. Here, since the target light has various wavelengths, it is desirable for the light reflectance of optical members to be minimized for specific wavelengths.
[0003] Furthermore, for pellicle frames for pellicles, which are optical components used in lithography processes, having a black or dark colored surface makes it easier and more reliable to inspect for foreign matter before use. In other words, from the perspective of inspectability, the surface of the pellicle frame is required to be black or dark colored.
[0004] In addition, with the recent trend toward finer patterns in LSIs, exposure light sources are becoming shorter in wavelength. These short-wavelength exposure light sources have high output and high light energy, so if inorganic acids such as sulfuric acid or phosphoric acid remain on the anodized film on the surface of the pellicle frame, they react with basic substances such as ammonia remaining in the exposure atmosphere to form reaction products (haze) such as ammonium sulfate. These reaction products cause clouding on the pellicle, which can affect the pattern transfer image.
[0005] Furthermore, many optical components are subject to sliding motion, and therefore it is necessary to provide the surface with excellent abrasion resistance and strictly suppress dust generation. That is, optical components are required to have many properties such as light weight, high rigidity, low reflectance, stability against light irradiation, environmental resistance, and abrasion resistance.
[0006] In response to this, for example, Patent Document 1 (JP 2010-237282 A) discloses a method for manufacturing a pellicle support frame formed from an aluminum material made of aluminum or an aluminum alloy, equipped with an optical thin film, and used as a pellicle, characterized in that an anodized film is formed on the surface of the aluminum material by anodizing treatment using an alkaline aqueous solution containing tartaric acid, followed by dyeing treatment using an organic dye, and then sealing treatment using water vapor.
[0007] In the manufacturing method of a pellicle support frame described in Patent Document 1, it is said that by anodizing an aluminum material using an alkaline aqueous solution containing tartaric acid without using sulfuric acid, which is the main cause of haze, it is possible to obtain a pellicle support frame that has excellent corrosion resistance and durability while minimizing the generation of haze.
[0008] Furthermore, Patent Document 2 (Japanese Patent Laid-Open Publication No. 07-43892) discloses a pellicle characterized in that the side surface or the entire surface of the pellicle frame is coated with paint by an electrodeposition coating method.
[0009] In the pellicle described in Patent Document 2, the sides or entire surface of the pellicle frame are coated with paint using an electrodeposition coating method, and the coating film is not uneven or porous like an anodized aluminum layer, but the coating surface is uniform and smooth, which is said to completely prevent dust generation during transportation or movement of the pellicle.
[0010] Furthermore, Patent Document 3 (JP 2016-177120 A) discloses a pellicle frame formed in a frame shape, made of a sintered body having a Young's modulus of 150 GPa or more and a Vickers hardness of 800 or more, in which the corner portions of the frame shape have a width greater than or equal to the width of the straight portions, and at least one of the corner portions has a width wider than the width of the straight portions, and the pellicle frame is made of ceramics, cemented carbide, or cermet.
[0011] The pellicle frame described in Patent Document 3 uses a sintered body with a high Young's modulus and Vickers hardness, which prevents the pellicle frame from being deformed by the membrane tension generated when the pellicle membrane is stretched over the pellicle frame. Moreover, since the width of at least one corner portion is wider than the width of the straight portion, the strength of the corner portion can be increased, further preventing deformation and damage to the pellicle frame. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] Japanese Patent Application Laid-Open No. 2010-237282 [Patent Document 2] Japanese Patent Application Publication No. 07-43892 [Patent Document 3] Japanese Patent Application Laid-Open No. 2016-177120 Summary of the Invention [Problem to be solved by the invention]
[0013] The pellicle frame described in Patent Document 1 above has excellent corrosion resistance, durability, and stability against light irradiation, and the pellicle frame described in Patent Document 2 above has improved dust generation, but does not take into consideration low reflectivity or the wear resistance of the outermost surface (the paint itself).
[0014] Furthermore, although the pellicle frame described in Patent Document 3 is endowed with high strength and rigidity, no study has been conducted on a method for achieving low reflectivity, stability against light irradiation, and abrasion resistance at the same time. In other words, the reality is that there are no suitable optical components that satisfy a wide range of requirements.
[0015] In view of the above-mentioned problems in the prior art, an object of the present invention is to provide a lightweight optical component that can be manufactured relatively inexpensively and has low reflectance, stability against light irradiation, and abrasion resistance, and an efficient method for manufacturing the same. [Means for solving the problem]
[0016] In order to achieve the above object, the present inventors have conducted extensive research into optical components and have discovered that it is extremely effective to form an appropriate low-reflectivity treated layer on the surface of a metal substrate and then form a silica layer on the surface of the low-reflectivity treated layer, thereby arriving at the present invention.
[0017] That is, the present invention provides: A metal substrate; a low-reflectivity treated layer formed on the surface of the metal substrate; a silica layer formed on the surface of the low reflectance treatment layer; The present invention provides an optical member characterized by the above.
[0018] In the optical element of the present invention, the silica layer present on the outermost surface imparts excellent abrasion resistance, and even if the low-reflectivity treatment layer is brittle, dust generation from the low-reflectivity treatment layer can be effectively suppressed.
[0019] Furthermore, in conventional optical components, a resin layer such as polyimide or acrylic is often formed on the outermost surface by electrodeposition coating, but the resin layer has low hardness and is unable to provide sufficient abrasion resistance. In contrast, a ceramic silica layer has sufficient hardness to achieve the abrasion resistance required for optical components.
[0020] Furthermore, even if a silica layer is formed, the low reflectance provided by the low-reflectance treatment layer can be maintained, and the components that cause haze can be prevented from being released to the outside. In other words, the provision of a dense silica layer on the outermost surface of a metal optical member is the greatest feature of the optical member of the present invention.
[0021] In the optical member of the present invention, the silica layer preferably has a thickness of 0.1 to 10 μm. By making the silica layer thickness 0.1 μm or more, a homogeneous silica layer with a uniform thickness can be formed, while by making the silica layer thickness 10 μm or less, the introduction of defects into the silica layer can be suppressed, ensuring toughness. Furthermore, the thickness of the silica layer is more preferably 0.5 to 1.5 μm. The method for forming the silica layer is not particularly limited as long as it does not impair the effects of the present invention, but for example, chemical vapor deposition (CVD) can be suitably used.
[0022] In the optical member of the present invention, the metal substrate is preferably made of aluminum or an aluminum alloy. By using aluminum or an aluminum alloy as the metal substrate, the optical member can be made lightweight. In addition, these metals have excellent formability and machinability, making it possible to realize inexpensive optical members having complex shapes.
[0023] In the optical element of the present invention, the metal substrate is preferably made of titanium or a titanium alloy. Titanium or a titanium alloy has a lower linear expansion coefficient than aluminum, and distortion during heating is effectively suppressed. Titanium or a titanium alloy also has a lower specific gravity than steel or cemented carbide, allowing the optical element to be lightweight. In addition, titanium or a titanium alloy is a metal material and has superior toughness compared to ceramics or cemented carbide, making it easy to handle. Furthermore, titanium or a titanium alloy has good processability, which allows for reduced manufacturing costs and provides high dimensional accuracy to the optical element.
[0024] In the optical member of the present invention, it is preferable that the low-reflectivity treatment layer is a porous layer. By using a porous layer as the low-reflectivity treatment layer, it is not necessary to use additional elements other than those contained in the metal substrate, and no additional measures are required for weather resistance, stability against light irradiation, etc. Here, while dust generation is generally a problem with porous layers, in the optical member of the present invention, dust generation is extremely effectively suppressed by the silica layer formed on the outermost surface.
[0025] Furthermore, in the optical member of the present invention, it is preferable that the increase in the reflectance of visible light due to the silica layer is 5% or less. By keeping the increase in the reflectance of visible light due to the silica layer 5% or less, the reflectance of the optical member can be made 10% or less.
[0026] The present invention also provides a low-reflectance treatment step in which a low-reflectance treatment layer is formed on the surface of the metal substrate by performing any one of dyeing treatment on the anodized film, electrolytic coloring treatment on the anodized film, thickness control of the anodized film, coating treatment with a low-reflectance film, and etching treatment using an aqueous solution containing one or more ions selected from the group consisting of fluoride ions, boron fluoride ions, and silicofluoride ions and a polar aprotic solvent; a surface coating treatment for forming a silica layer having a thickness of 0.1 to 10 μm on the surface of the low reflectivity treatment layer by a chemical vapor deposition method; Also provided is a method for producing an optical member, characterized by:
[0027] In the method for producing an optical member of the present invention, a low-reflectance treated layer can be easily formed on the surface of a metal substrate by performing any of the following in the low-reflectance treatment step: dyeing the anodized film, electrolytic coloring the anodized film, controlling the film thickness of the anodized film, coating the anodized film with a low-reflectance film, or etching using an aqueous solution containing one or more ions selected from the group consisting of fluoride ions, boron fluoride ions, and silicofluoride ions and a polar aprotic solvent. In particular, when the metal substrate is titanium or a titanium alloy, etching using an aqueous solution containing one or more ions selected from the group consisting of fluoride ions, boron fluoride ions, and silicofluoride ions and a polar aprotic solvent can form a porous low-reflectance treated layer while suppressing the introduction of substances that cause haze.
[0028] Furthermore, in the method for manufacturing an optical member of the present invention, a uniform, dense, and defect-free silica layer having a thickness of 0.1 to 10 μm can be formed on the surface of the low-reflectivity treatment layer by using chemical vapor deposition (CVD). The type and process conditions of the chemical vapor deposition method are not particularly limited as long as they do not impair the effects of the present invention; the conditions for forming a good silica layer having a thickness of 0.1 to 10 μm can be appropriately adjusted. Examples of chemical vapor deposition methods that can be used include thermal CVD, plasma-induced CVD, photo-CVD, atmospheric pressure CVD, low-pressure CVD, and combinations thereof. Other methods that can be used to form the silica layer include physical vapor deposition (PVD), immersion, spin coating, and spray coating.
[0029] In addition, in the method for producing an optical element of the present invention, it is preferable to adjust the reflectance of visible light corresponding to a desired wavelength to 10% or less by adjusting the thickness of the silica layer. When the present inventors evaluated the relationship between total reflectance and wavelength of light for the optical element of the present invention, they found that the total reflectance of an optical element obtained under specific conditions varies depending on the wavelength, and that a graph with the vertical axis representing total reflectance and the horizontal axis representing wavelength of light appears wavy. Furthermore, a phenomenon was observed in which the curve shifted toward the horizontal axis (wavelength of light) depending on the film thickness of the silica layer. These results indicate that the total reflectance of any wavelength can be adjusted to a low value by adjusting the thickness of the silica layer.
[0030] In the method for manufacturing an optical element of the present invention, the metal substrate is preferably made of any one of aluminum, an aluminum alloy, titanium, and a titanium alloy. By using aluminum or an aluminum alloy as the metal substrate, the optical element can be made lightweight. Furthermore, these metals have excellent formability and machinability, making it possible to realize inexpensive optical elements having complex shapes. Furthermore, titanium or a titanium alloy has good processability, making it possible to reduce manufacturing costs and to provide optical elements with high dimensional accuracy. [Effects of the Invention]
[0031] According to the present invention, it is possible to provide a lightweight optical element that can be manufactured relatively inexpensively and has low reflectance, stability against light irradiation, and abrasion resistance, and an efficient method for manufacturing the same. [Brief explanation of the drawings]
[0032] [Figure 1] 1 is a schematic cross-sectional view of an optical member according to an embodiment. [Figure 2] 1 is a graph showing the reflectance of an example optical member 1. [Figure 3] 10 is a graph showing the reflectance of an example optical member 2. DETAILED DESCRIPTION OF THE INVENTION
[0033] Representative embodiments of the optical component and its manufacturing method of the present invention will be described in detail below with reference to the drawings, but the present invention is not limited to these. Furthermore, some or all of the components in the embodiments can be combined as appropriate. In the following description, identical or equivalent parts are designated by the same reference numerals, and redundant explanations may be omitted. Furthermore, since the drawings are intended to conceptually explain the present invention, the dimensions and ratios of the components shown may differ from the actual dimensions.
[0034] 1. Optical components Optical members come in a wide variety of shapes and sizes, but a schematic cross-sectional view of a simple plate-shaped optical member is shown in Figure 1. The optical member 1 has a metal substrate 2, a low-reflectivity treated layer 4, and a silica layer 6. The low-reflectivity treated layer 4 is formed on the surface of the metal substrate 2, and the silica layer 6 is formed on the surface of the low-reflectivity treated layer 4.
[0035] The material of the metal substrate 2 is not particularly limited as long as it does not impair the effects of the present invention, and various conventionally known metal materials can be used. However, from the viewpoints of light weight, formability, cost, etc., aluminum or an aluminum alloy is preferred, and from the viewpoints of distortion suppression during heating, rigidity, dimensional accuracy, etc., titanium or a titanium alloy is preferred.
[0036] When the metal substrate 2 is made of aluminum or an aluminum alloy, examples of the 1000 series aluminum include A1050, A1050A, A1070, A1080, A1085, A1100, A1200, A1N00, and A1N30 as specified in the JIS standard, examples of the 3000 series aluminum alloy include A3003, A3103, A3203, A3004, A3104, A3005, and A3105 as specified in the JIS standard, and examples of the 5000 series aluminum alloy include A1000, A1000, A1001, A1002, A1003, A1004, A1005, and A1006 as specified in the JIS standard. Examples of the 6000 series aluminum include A6101, A6003, A6005, A6N01, A6151, and A6063 described in the JIS standard, and examples of the 7000 series aluminum alloy include A7001, A7003, A7005, A7010, A7020, A7049, A7050, A7075, A7090, A7091, A7178, A7475, and A7N01.
[0037] When the metal substrate 2 is titanium or a titanium alloy, various commercially pure titanium (types 1 to 4), Ti-6Al-4V alloy, Ti-6Al-6V-2Sn alloy, Ti-6Al-2Sn-4Zr-6Mo alloy, Ti-10V-2Fe-3Al alloy, Ti-7Al-4Mo alloy, Ti-5Al-2.5Sn alloy, Ti-6Al-5Zr-0.5Mo-0.2Si alloy, Ti-5.5Al-3.5Sn-3Zr-0.3 Mo-1Nb-0.3Si alloy, Ti-8Al-1Mo-1V alloy, Ti-6Al-2Sn-4Zr-2Mo alloy, Ti-5Al-2Sn-2Zr-4Mo-4Cr alloy, Ti-11.5Mo-6Zr- Examples include 4.5Sn alloy, Ti-15V-3Cr-3Al-3Sn alloy, Ti-15Mo-5Zr-3Al alloy, Ti-15Mo-5Zr alloy, and Ti-13V-11Cr-3Al alloy.
[0038] When the metal substrate 2 is aluminum or an aluminum alloy, the low-reflectivity treatment layer 4 may be formed, for example, by forming a suitable anodized film on the surface of the metal substrate 2 and then dyeing it using electrolytic coloring or organic dyes. Alternatively, a low-reflectivity film having a low reflectivity may be coated by an appropriate method. When the metal substrate 2 is titanium or a titanium alloy, for example, a low-reflectivity treatment layer 4 may be formed by making the surface of the metal substrate 2 porous or by forming an anodized film having an appropriate thickness, thereby utilizing light interference. Alternatively, a low-reflectivity film having a low reflectivity may be coated by an appropriate method. That is, while it is necessary to achieve low reflectivity with the low-reflectivity treatment layer 4, it is sufficient to form an appropriate layer taking into account the type of metal substrate 2, manufacturing costs, etc.
[0039] The silica layer 6 is formed on the surface of the low reflectance treatment layer 4, and preferably has a thickness of 0.1 to 10 μm. By making the thickness of the silica layer 6 0.1 μm or more, it is possible to achieve a homogeneous and uniform state of thickness, and by making the thickness 10 μm or less, it is possible to suppress the introduction of defects into the silica layer 6 and ensure toughness.
[0040] Furthermore, since the silica layer 6 determines the abrasion resistance and scratch resistance of the optical member 1, the hardness of the silica layer 6 is preferably 250 HV or more, more preferably 300 HV or more, and most preferably 350 HV or more. Here, the hardness of the silica layer 6 may be a value measured from the surface of the optical member 1 using a micro Vickers hardness tester. More specifically, for example, the hardness obtained by applying an indenter load of 0.05 g and holding the load for 15 seconds can be used.
[0041] The reflectance of the optical member 1 is preferably 10% or less, more preferably 8% or less, for the target light. A reflectance of 10% or less can adequately suppress light reflection in various optical instruments, pellicle frames, and the like. These reflectances are preferably satisfied for the wavelength of light required for the application of the optical member. For example, when targeting LED light, the reflectance is preferably satisfied in the range of 500 to 550 nm. Furthermore, suppressing reflected light, including visible light, allows for good optical observation of the optical member using a camera. In this specification, reflectance refers to a value measured by the method described in the Examples.
[0042] In addition, the lightness index (L * The surface brightness index L (value: brightness index according to Hunter's color difference formula) is preferably 50 or less, and more preferably 40 or less. * By setting the value to 50 or less, it is possible to sufficiently suppress the light reflection of various optical components. In addition, in the case of a pellicle frame, inspection for foreign matter before use can be easily and reliably performed. In this specification, the brightness index L * The values refer to values measured by the methods described in the Examples.
[0043] Furthermore, since the surface of the optical member 1 is covered with the silica layer 6, the amount of ions eluted from the optical member 1 is extremely small. In an ion elution test in which the optical member 1 is immersed in 100 ml of pure water at 90°C for 3 hours to measure the concentration of eluted ions, 2 It is preferable that the concentrations of acetate ions, formate ions, chloride ions, nitrate ions, nitrite ions, and ammonium ions be 10 ppb or less, 100 ppb or less, 200 ppb or less, 10 ppb or less, 10 ppb or less, 10 ppb or less, and 10 ppb or less, respectively, eluted into 100 ml of pure water per 100 ml of pure water. By controlling the elution amounts of these ions, the generation of haze can be reduced as much as possible.
[0044] Examples of the optical member 1 include a pellicle frame, a lens holder, a barrel, a shade, and a reflector.
[0045] 2. Manufacturing method of optical components The method for producing an optical member of the present invention includes a low-reflectivity treatment step (S01) of subjecting a metal substrate 2 to any of the following treatments: dyeing an anodized film, electrolytic coloring an anodized film, controlling the film thickness of an anodized film, coating a low-reflectivity film, or etching using an aqueous solution containing one or more ions selected from the group consisting of fluoride ions, boron fluoride ions, and silicofluoride ions and a polar aprotic solvent, thereby forming a low-reflectivity treatment layer 4 on the surface of the metal substrate 2; and a surface coating treatment (S02) of forming a silica layer 6 having a thickness of 0.1 to 10 μm on the surface of the low-reflectivity treatment layer 4 by a chemical vapor deposition method.
[0046] (1) Low reflectivity treatment process (S01) The purpose of the low reflectance treatment step (S01) is to form a low reflectance treatment layer 4 on the surface of the metal base 2 and reduce the reflectance of the surface of the metal base 2.
[0047] The method for the low-reflectance treatment is not particularly limited as long as it does not impair the effects of the present invention, and various conventionally known treatment methods may be used. Here, when the metal substrate 2 is titanium or a titanium alloy, a porous layer can be formed on the surface of the metal substrate 2 by etching using an aqueous solution containing one or more ions selected from the group consisting of fluoride ions, borofluoride ions, and silicofluoride ions and a polar aprotic solvent, thereby achieving a reduction in reflectance and blackening.
[0048] Furthermore, as a pretreatment for the low reflectance treatment, the surface of the metal substrate 2 may be roughened or chemically polished. For example, roughening can be performed by shot blasting using an appropriate media, and chemical polishing can be performed by etching using an appropriate etching solution.
[0049] (2) Surface coating treatment (S02) The purpose of the surface coating treatment (S02) is to form a silica layer 6 on the outermost surface of the optical member 1, thereby imparting excellent abrasion resistance and scratch resistance to the optical member 1 and suppressing ion elution from the interior. In this process, it is also necessary to suppress an increase in the reflectance and brightness index that were reduced by the low-reflectance treatment step (S01).
[0050] By using chemical vapor deposition (CVD), a homogeneous, dense, and defect-free silica layer 6 having a thickness of 0.1 to 10 μm can be formed on the surface of the low-reflectivity treatment layer 4. The type and process conditions of the chemical vapor deposition method are not particularly limited as long as they do not impair the effects of the present invention. Conditions for forming a good silica layer 6 having a thickness of 0.1 to 10 μm can be appropriately adjusted. Examples of chemical vapor deposition methods that can be used include thermal CVD, plasma-induced CVD, photo-CVD, atmospheric pressure CVD, low-pressure CVD, and combinations of these. Other methods that can be used to form the silica layer 6 include physical vapor deposition (PVD), immersion, spin coating, and spray coating.
[0051] As described above, the reflectance of the optical member 1 can be adjusted by the thickness of the silica layer 6. The thickness of the silica layer 6 can be easily changed by adjusting the CVD conditions, such as the processing time, processing temperature, and processing atmosphere. When the silica layer 6 is formed on a lens or the like using a CVD method, the thickness of the silica layer 6 is often limited to approximately several tens to several hundreds of nanometers. However, the thickness of the silica layer 6 is 0.1 to 10 μm, and therefore, compared to conventional general CVD conditions, the processing time must be longer, for example.
[0052] Representative embodiments of the present invention have been described above, but the present invention is not limited to these, and various design modifications are possible, all of which are included in the technical scope of the present invention. [Example]
[0053] Example 1 A 50mm x 50mm x 3mm A7075 aluminum alloy plate was roughened by spraying with stainless steel media at a pressure of 0.1 MPa. An anodized film was then formed using a solution containing tartaric acid, followed by a dyeing process to form a low-reflectivity coating. The anodized film was electrolyzed for 20 minutes at a constant voltage of 40 V in an alkaline aqueous solution (pH = 13.0) containing 53 g / L of sodium tartrate dihydrate (Na2C4H4O6·2H2O) and 4 g / L of sodium hydroxide. After rinsing with pure water, the anodized film formed on the surface of the A7075 aluminum alloy plate was measured using an eddy current film thickness gauge (Fisher Instruments) to determine its thickness, which was 6.6 μm.
[0054] For the dyeing treatment, the anodized A7075 aluminum alloy plate was immersed in an aqueous solution containing an organic dye (TAC411 manufactured by Okuno Pharmaceuticals) at a concentration of 10 g / L at 55°C for 10 minutes.
[0055] Next, a silica layer was formed on the surface of the low-reflectivity treatment layer using a chemical vapor deposition method (plasma CVD method). Specifically, a gaseous precursor mixture containing a silane compound, oxygen, and a radical scavenger was circulated near the A7075 aluminum alloy sheet, and the gaseous precursor mixture was reacted on the surface of the A7075 aluminum alloy sheet at approximately 600°C to form a silica layer with a thickness of 1 μm, thereby obtaining an example optical element 1.
[0056] <Example 2> A 50 mm × 50 mm × 1 mm plate made of commercially pure titanium (type 2) was subjected to a surface roughening treatment in the same manner as in Example 1. Thereafter, an etching treatment was performed for 240 seconds using an aqueous solution containing fluoride ions and a polar aprotic solvent, to form a porous low-reflectivity treated layer.
[0057] Next, in the same manner as in Example 1, a silica layer having a thickness of 1 μm was formed on the surface of the low reflectance treatment layer, thereby obtaining an example optical member 2.
[0058] <Comparative Example 1> After the surface roughening treatment, a low-reflectance treatment layer was formed in the same manner as in Example 1. Next, a polyimide layer was formed on the surface of the low-reflectance treatment layer by electrodeposition coating, thereby obtaining a comparative optical member 1. Here, the electrodeposition coating conditions were a treatment voltage of 200 V and a treatment time of 3 minutes.
[0059] <Comparative Example 2> A comparative optical member 2 was obtained in the same manner as in Comparative Example 1, except that an acrylic layer was formed on the surface of the low reflectance treatment layer by electrodeposition coating. Here, the electrodeposition coating conditions were a treatment voltage of 100 V and a treatment time of 3 minutes.
[0060] <Comparative Example 3> Comparative optical member 3 was obtained in the same manner as in Example 1, except that no silica layer was formed.
[0061] <Comparative Example 4> A comparative optical member 4 was obtained in the same manner as in Example 2, except that no silica layer was formed.
[0062] [evaluation] 1. Brightness index Using a brightness measuring instrument (manufactured by Nippon Denshoku Industries Co., Ltd., NF777), the brightness index L of the example optical members 1 and 2 and the comparative optical member 1 was measured. * The results are shown in Table 1.
[0063] [Table 1]
[0064] As shown in Table 1, the Example Optical Members 1 and 2 on which a silica layer was formed had a lower L than the Comparative Optical Member 1 on which a resin layer (polyimide layer) was formed. * Although the value is increasing, it can be seen that values below 40 are obtained.
[0065] 2.Reflectance The reflectance of the exemplary optical members 1 and 2 was measured using a reflectance meter (Lambda 750, manufactured by PerkinElmer). The measurement results for the exemplary optical member 1 are shown in FIG. 2, and the measurement results for the exemplary optical member 2 are shown in FIG. 3. For the exemplary optical member 1, eight samples prepared under the same conditions were measured, and for comparison, the state before the silica layer was formed was also measured. For the exemplary optical member 2, four samples prepared under the same conditions were measured, and for comparison, the state before the silica layer was formed was also measured.
[0066] 2, the reflectance of the embodied optical element 1 varies little depending on the wavelength of the target light and between measurement samples, being a low value of around 10%. Furthermore, almost no increase in reflectance due to the formation of the silica layer is observed.
[0067] 3, the reflectance of the embodied optical element 2 varies depending on the wavelength of the target light, fluctuating between 5 and 30%. The extent of this increase or decrease differs depending on the sample being measured, but this is dependent on the thickness of the silica layer. By slightly changing the thickness of the silica layer, the reflectance for a specific wavelength can be adjusted to a low value (10% or less). From this perspective, the formation of the silica layer hardly increases the reflectance.
[0068] 3. Dust generation evaluation The dust generation characteristics of Example Optical Members 1 and 2 and Comparative Optical Members 3 and 4 were evaluated. Specifically, they were immersed in pure water and subjected to ultrasonic cleaning for one minute, and then the number of particles in 3 L of the pure water was measured using a particle counter (NP500T manufactured by Nippon Denshoku Industries Co., Ltd.). The number of particles with a particle size of 0.5 μm or more is shown as a relative comparison in Table 2. Here, Example Optical Member 1 and Comparative Optical Member 3, Example Optical Member 2, and Comparative Optical Member 4 differ in the presence or absence of a silica layer. Therefore, to clarify the effect of the silica layer, the relative value of the particle number of Example Optical Member 1 when the particle number of Comparative Optical Member 3 is set to 1, and the relative value of the particle number of Example Optical Member 2 when the particle number of Comparative Optical Member 4 is set to 1 are shown, respectively.
[0069] [Table 2]
[0070] As shown in Table 2, the number of particles with a particle size of 0.5 μm or more is significantly reduced by the formation of the silica layer, with a 30% reduction when comparing Example Optical Element 1 with Comparative Optical Element 3, and a 40% reduction when comparing Example Optical Element 2 with Comparative Optical Element 4.
[0071] 4. Amount of ion elution The amount of ion elution was evaluated for Example Optical Members 1 and 2 and Comparative Optical Member 2. Specifically, these were immersed in 100 ml of pure water and subjected to a heat treatment at 90°C for 3 hours. The amount of ions in the eluate (pure water) was then measured using an ion chromatograph. The amount of ion elution per 100 ml of pure water is shown in Table 3. The unit of the amount of ion elution is ppb.
[0072] [Table 3]
[0073] As shown in Table 3, the amount of ion elution from Example Optical Members 1 and 2 was generally small, with sulfate ions and NH ions showing no problem. Comparing Example Optical Member 1 and Comparative Optical Member 2, which have similar configurations except for the outermost surface layer, it can be seen that Example Optical Member 1, which has a silica layer on the outermost surface, effectively suppresses the elution of acetic acid and formic acid.
[0074] 5.Hardness measurement Using a micro Vickers hardness tester (Mitutoyo Corporation, HM-221), the surface hardness of the example optical members 1 and 2 and the comparative optical members 1, 2, and 4 was measured under the conditions of an applied load of 0.05 g and a holding time of 15 seconds. The hardness measurement was performed five times, and the obtained results are shown in Table 4.
[0075] [Table 4]
[0076] As shown in Table 4, when comparing the average Vickers hardness values of Example Optical Component 1, Comparative Optical Component 1, and Comparative Optical Component 2, which are based on A7075 aluminum alloy plate material, Example Optical Component 1 is 333 Hv, Comparative Optical Component 1 is 299 Hv, and Comparative Optical Component 2 is 256 Hv, which shows that providing a silica layer on the outermost surface provides excellent wear resistance.
[0077] Furthermore, when comparing the average Vickers hardness of Example Optical Component 2 and Comparative Optical Component 4, which are both based on commercially pure titanium (type 2) plate material, Example Optical Component 2 has a hardness of 288 Hv and Comparative Optical Component 4 has a hardness of 197 Hv, indicating that excellent wear resistance is imparted by providing a silica layer on the outermost surface.
[0078] Here, when comparing the average Vickers hardness values of Example Optical Component 1 and Example Optical Component 2, which have a silica layer on the outermost surface, it is found that Example Optical Component 1, which has an A7075 aluminum alloy plate as the base material, has a higher hardness, and it is clear that under the measurement conditions used here, the mechanical properties of the base material affect the Vickers hardness even when a silica layer is provided on the outermost surface. [Explanation of symbols]
[0079] 1. Optical member, 2...metal base material, 4. Low reflectivity treatment layer, 6···Silica layer.
Claims
1. A metal substrate; A low reflectance treated layer formed on the surface of the metal base material; a silica layer formed on the surface of the low reflectance treatment layer, the silica layer is formed by a thermal CVD method, a plasma-induced CVD method, a photo-CVD method, an atmospheric CVD method, a low-pressure CVD method, or a combination thereof; The thickness of the silica layer is 0.5 to 1.5 μm; The hardness of the silica layer is 250 HV or more, The reflectance of visible light is 3 to 10%, In an ion elution test in which the concentration of eluted ions is measured after immersion in 100 ml of pure water at 90°C for 3 hours, the elution concentrations in 100 ml of pure water per 50 cm2 of surface area are 100 ppb or less of acetate ion, 200 ppb or less of formate ion, 10 ppb or less of chloride ion, 10 ppb or less of nitrate ion, 10 ppb or less of nitrite ion, and 10 ppb or less of ammonium ion; An optical component comprising:
2. The metal substrate is made of aluminum or an aluminum alloy; The optical member according to claim 1 .
3. The metal substrate is made of titanium or a titanium alloy; The optical member according to claim 1 .
4. an increase in visible light reflectance due to the silica layer being 5% or less; 3. The optical member according to claim 1 or 2,
5. a low reflectance treatment step of forming a low reflectance treatment layer on the surface of the metal substrate by performing any one of a dyeing treatment on the anodized film, an electrolytic coloring treatment on the anodized film, an anodizing treatment, a coating treatment with a low reflectance film, and an etching treatment using an aqueous solution containing one or more ions selected from the group consisting of fluoride ions, boron fluoride ions, and silicofluoride ions, and a polar aprotic solvent; a surface coating process for forming a silica layer having a thickness of 0.5 to 1.5 μm and a hardness of 250 HV or more on the surface of the low reflectance treatment layer by a thermal CVD process, a plasma-induced CVD process, a photo-CVD process, an atmospheric pressure CVD process, a reduced pressure CVD process, or a combination thereof; The metal substrate is made of any one of aluminum, an aluminum alloy, titanium, and a titanium alloy, The reflectance of visible light is 3 to 10%. A method for producing an optical member, comprising the steps of:
Citation Information
Patent Citations
Personal ornaments
JP1988213695A
Composite film of anodically oxidized ti film and metallic oxide thin film
JP1992341581A
Pellicle
JP1995043892A
Exterior part of wrist watch and its manufacturing method
JP2005076092A
Transparent resin laminate and method of manufacturing the same
JP2010049050A
